DIODE LASER GINGIVAL PEELING. CASE REPORT - Enciso Lupuche, Daniel (2026)
In modern dentistry, esthetics plays a crucial role in the well-being of patients, since a harmonious　smile, including lips, teeth and gums, directly impacts self-confidence. The gingiva normally has a　pink or coral color but can darken due to endogenous factors (such as genetics and melanogenesis)　or exogenous factors (such as medications, smoking and systemic diseases). When the gingiva　darkens excessively, this is gingival hyperpigmentation, which is characterized by brown spots.　To correct this, several treatments have been developed, including laser surgery, which is effective,　precise and less invasive. In this context, a case is presented in which a diode laser was used to perform a “gingival peel” at a public university in Peru. The case is presented of a 64-year-old　patient of African descent, smoker and native of Lima, with a history of Poliomyelitis and a surgical　intervention on the spine due to the sequelae, which caused motor disability. The patient went to　the Comprehensive Adult Clinic IV (CIA IV) of the Faculty of Dentistry of the Universidad　Nacional Mayor de San Marcos (UNMSM), accompanied by her friend, due to the absence　of teeth and the lack of esthetics in the anterior sector. The effectiveness of laser therapy in the　treatment of gingival peeling is concluded, highlighting the key role of the diode laser in obtaining　positive results. The procedure was safe, simple and fast, according to several sources. In addition, it　favored a postoperative period without pain or bleeding, reduced healing time and allowed recovery　with minimal discomfort, improving patient satisfaction and comfort.